Effect of cold-pressed hazelnut cake incorporation on the quality characteristic of meat emulsion system and its potential application for frankfurter-type beef sausages - Atalar, İlyas (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2024)
This research was performed to investigate the effect of hazelnut cake (HC) as a cold press waste product on the physicochemical and textural properties of the frankfurter-type sausages during cold storage. According to the highest emulsion capacity (174.14 mL oil/g), emulsion stability (79.86%), and optimum rheological results obtained in emulsions, 1% HC concentration was selected for the utilization in the sausage formulation. HC added sausage was compared with the control sample at 4 °C for 60 days of storage. HC addition increased the hardness and chewiness properties and decreased weight loss of sausages during storage. The incorporation of HC in formulation slowed down the increase in malondialdehyde and conjugated dienes concentrations after the 15th day of storage compared to the control sausages. The results demonstrated that HC presented a good opportunity for protecting the quality parameters of emulsified meat products during storage